Answer:
the answer to your question should be 2,068
Step-by-step explanation:
i hope i am right but i think so
To find the solution to this problem, you would do the opposite of division which is multiplication.
Use the terms you have to plug into your new equation;
0.6 x 1.4 = .84
To check your work you would plug in .84 where the '?' is;
.84/.6= 1.4
There you have the original equation you began with.
Therefore, .84 would be your final answer.
Answer:
The average rate of change of the given function
A(x) = 1
Step-by-step explanation:
<u><em>Step(i):-</em></u>
Given function f(x) = x² - 2x -4
And given that x = a = -1 and x=b = 4
The average rate of change of the given function
![A(x) = \frac{f(b)-f(a)}{b-a}](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D)
<u><em>Step(ii):-</em></u>
f(x) = x² - 2x -4
f(-1) = (-1)² - 2(-1) -4 = 1+2-4 = -1
f(4) = 4² -2(4) -4 = 16 -12 = 4
The average rate of change of the given function
![A(x) = \frac{f(b)-f(a)}{b-a}](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D)
![A(x) = \frac{4-(-1)}{4-(-1)} = \frac{5}{5} = 1](https://tex.z-dn.net/?f=A%28x%29%20%3D%20%5Cfrac%7B4-%28-1%29%7D%7B4-%28-1%29%7D%20%3D%20%5Cfrac%7B5%7D%7B5%7D%20%3D%201)
<u><em>final answer:-</em></u>
The average rate of change of the given function
A(x) = 1
Number 1 is C.
Number 2 is C.
Did you need all of them?
Answer:
(6-√21, 6+√21)
Step-by-step explanation:
x^2 - 12x = -15
(x - 6)^2 - 36 = -15
(x - 6)^2 = 21
x - 6 = ± √21
x = 6 ± √21